Designing mobile experiences for collocated interaction - Lundgren, Sus; Fischer, Joel; Reeves, Stuart; Torgersson, Olof (2015)
Many of our everyday social interactions involve mobile devices. Yet, these tend to only provide good support for distributed social interactions. Although much HCI and CSCW research has explored how we might support collocated, face-to-face situations using mobile devices, much of this work exists as isolated exemplars of technical systems and / or interaction designs. This paper draws on a range of such exemplars to develop a practical design framework intended for guiding the design of new mobile experiences for collocated interaction as well as analysing existing ones. Our framework provides four relational perspectives for designing the complex interplay between: the social situation in which it takes place; the technology used and the mechanics inscribed; the physical environment; and the temporal elements of design. Moreover, each perspective is features some core properties, which are highly relevant when designing these systems. As part of presenting the framework we also explain the process of its construction along with practical advice on how to read and apply it.